MR/FEATURES AND RESECTABILITY PREDITION OF ESOPHAGEAL CARCINOMA - Kong, Xiangquan; Luo, hanchao; Peng, Zhenjun; Liu, Dingxi (Chinese Journal of Cancer Research, 2013)
To evaluate MRI in esophageal carcinoma and its resectability. MR imaging (sagittal, coronal, axial) were performed in 30 cases (male 24 cases, female 6 cases, average age 58 years) and retrospectively analyzed. Results showed that MRI clearly demonstrated the location, actual length, and extent of esophageal carcinoma as well as its relation with surrounding structures in all cases. Metastasis to other organs was found in 7 cases. The conclusion indicated that MR imaging played an important role in preoperative diagnosis of esophageal carcinoma, providing valuable information in determining resectability of the tumor.